The businessman as a consumer in Argentina and its analysis in comparative legislation - Arias Cáu, Esteban Javier (2024)
The legal relation of consumption, as a species of the relation of obligation, is a fundamental notion in the development of the right of defense of the consumer and has normative support throughout Latin America, either constitutional or legal, which allows to obtain a common language and this has interesting repercussions in the progress of the discipline. However, the object of the present work is more restricted in view of the fact that it consists in inquiring into the notion of consumer, their classifications and technical discussions about a concept that has points of contact with the trader or entrepreneur and which some doctrine calls as mixed consumer or entrepreneur.